2021
DOI: 10.3389/fphar.2021.663322
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Regulating Mitochondrial Function in Cardiac Diseases

Abstract: Mitochondria are the key organelles that supply cellular energy. As the most active organ in the body, the energy required to maintain the mechanical function of the heart requires a high quantity of high-quality mitochondria in cardiomyocytes. MicroRNAs (miRNAs) are single-stranded noncoding RNAs, approximately 22 nt in length, which play key roles in mediating post-transcriptional gene silencing. Numerous studies have confirmed that miRNAs can participate in the occurrence and development of cardiac diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 150 publications
0
19
0
Order By: Relevance
“…Several miRNAs are specifically associated with the mitochondrial phenotype in human diseases (Zhang et al, 2021). Some of them, also known as mitomiRs, are produced by the mitochondrial genome to regulate the mRNA transcription in loco, others can target nuclear encoded mRNAs localized on the mitochondria surface, or are necessary for mitochondrial homeostasis (Latronico and Condorelli, 2012;Song et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several miRNAs are specifically associated with the mitochondrial phenotype in human diseases (Zhang et al, 2021). Some of them, also known as mitomiRs, are produced by the mitochondrial genome to regulate the mRNA transcription in loco, others can target nuclear encoded mRNAs localized on the mitochondria surface, or are necessary for mitochondrial homeostasis (Latronico and Condorelli, 2012;Song et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Placental microRNAs (miRNAs) are selectively packaged in the exosomes, secreted into the maternal and fetal circulation and transferred to target cells where they regulate gene expression [ 68 ]. Recent evidence suggests that miRNAs regulate GLUT1 expression as well as cardiac mitochondrial function [ 69 , 70 , 71 ]. Moreover, BPA alters the expression of several small RNAs in the mouse placentas [ 68 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various miRNAs have been described to contribute to distinct CVDs, such as HF, ischemic heart diseases, cardiac hypertrophy and diabetic cardiomyopathy, through the regulation of relevant signaling pathways and mitochondrial function-related proteins [ 49 ]. In this regard, several studies that used transgenic mice with overexpressed specific miRNA activity have demonstrated a crucial role in the initiation and progression of DCM through regulating genes involved in the maintenance of mitochondrial function ( Figure 1 and Table 1 ).…”
Section: Mitochondria Dysfunction and Mirnasmentioning
confidence: 99%